Kriticeskie zametki po probleme bioenergeticeskogo spektra rezimov begovoj nagruzki - Kizko, A. P.; Kizko, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
From the point of view of the modern poly system model of the substantiation of the scientific knowledge the theory divides into the levels based on the empirical and theoretical grounds.